The impact of conferencing assessment on efl students’ grammar learning (2012)
This article reports on a study that was carried out in order to examine the impact of conferencing assessment on students’ learning of English grammar. Forty-two Iranian intermediate university students were randomly assigned to an experimental and a control group. The participants in the experimental group took part in four individual and four whole class conferences. The participants in the control group studied the same grammatical points but they were not involved in conferencing assessment. The results of the study showed that the experimental group performed significantly better than the control group on the given post-test. Moreover, the attitudes of the participants toward grammar learning in the experimental group significantly changed from the first administration of a questionnaire to its second administration. En este artículo se reporta un estudio llevado a cabo con el fin de examinar el impacto de la evaluación mediante conferencias en el aprendizaje de gramática inglesa. Cuarenta y dos estudiantes universitarios iraníes, de nivel intermedio, fueron asignados aleatoriamente a dos grupos: uno experimental y otro de control. Los estudiantes del grupo experimental participaron en cuatro entrevistas individuales y cuatro con toda la clase. Los del grupo de control estudiaron los mismos elementos gramaticales perono estuvieron involucrados en conferencias de evaluación. Los resultados del estudio mostraron que el grupo experimental tuvo un desempeño significativamente mejor que el del grupo de control en el examen que se realizó al final del proceso investigativo. Además, se halló que las actitudes de los participantes del grupo experimental hacia el aprendizaje de la gramática cambiaron entre la primeray la segunda aplicación de un cuestionario.